Some problems of improvement of corporate relations are in joint-stock companies - Вінник, Оксана Мар’янівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article is devoted to the problems of improvement of the legal regulation of corporate relations in connection with entry into force of the Law of Ukraine «On joint-stock companies» and by the prospect of development of public-private partnership in Ukraine.